THE PRACTICE OF INNOVATIVE INFORMATION TECHNOLOGY TO IMPROVE THE EFFICIENCY OF THE INSTITUTION OF BANKRUPTCY - A. R. Gareev (Модернизация, инновация, развитие, 2015)
The practical use of these innovations, the benefits of implementing information technology in bankruptcy, as well as prospects for the application of such technologies in the field of bankruptcy regulations are covered in this article.